Reflective essay on bees in plants: analysis of textbooks of elementary school (Research, Society and Development, 2022)
This work presents an analysis of the plant unit: plant reproduction, bees and environmental preservation in textbooks of the second year of elementary school. For the study were selected four didactic works of different authors of the 2017 editions, approved by the National Plan of the Didactic Book (PNLD-2019), the qualitative evaluation was organized in 4 categories: contents, visual resources, extra activities, questions and knowledge. In the content approach, it was verified the absence of important information regarding the themes of plant reproduction, bee and environmental preservation, requiring pedagogical intervention by the educator. The visual resource in some materials showed possible errors or misunderstandings regarding the pollination process and images that do not complement the reproductive process of plants. Environmental preservation was highlighted in most books, showing care for the environment, preservation of forests, recycling and composting of organic waste. This analysis is not intended to declassify or demystify the works, but to contribute to the editorial authors on the need to address in the plant unit the importance of bees, the pollination process, and contextualized issues about environmental problems.